ORGANIZATION OF CORRECT TREATMENT OF PATIENTS WITH PROXIMAL FEMORAL FRACTURES - V. V. Klyuchevskiy; M. V. Belov; S. V. Bystrov; I. A. Serov (Travmatologiâ i Ortopediâ Rossii, 2016)
A retrospective analysis of the quality of specialized care provided to 820 patients with proximal femur fractures (PFF) at Solovyov Hospital (Yaroslavl) in 2013 was performed. A direct relationship was established between the time elapsed from the injury to hospital admission and the rate of vein thrombosis of the lower limbs. Operative activity in the treatment of patients with this pathology was 91.7%. A need for different implants for operative treatment of patients with this injury per 100,000 population was determined. Operative treatment of PFF in elderly and old-aged people should be considered a life-saving procedure to be performed on urgent indications(within 24 to 48 hours since the injury).